2021
DOI: 10.18186/thermal.888428
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Heat Transfer Characteristics of Porous Type Copper Heat Sink With Bifurcations

Abstract: The lotus type porous copper heat sink has a higher heat transfer capacity as compared to micro channel heat sink for same size. Many studies on this heat sink show that its heat transfer capacity can be further improved by improving design of heat sink. This study investigates the heat transfer and flow characteristics of porous heat sink with different designs of internal bifurcations under both laminar & turbulent flow and studies the effect of such bifurcations on heat transfer of heat sink. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Different manufacturing techniques also play an important role in the design of heat sinks; for example, pin-type geometry with addi-tive manufacturing was designed and its effects analyzed [10]. Thangavel and Sekar [11] designed a lotus-type heat sink, analyzed the temperature distributions in laminar and turbulent flow, and observed that they decreased up to 302 K. Nanofluids (NFs) are being used more and more to improve heat transfer in different HS setups because to their high thermal conductivity and density. The computational study conducted by Kavitha et al [12] demonstrated a significant 68% enhancement in heat transfer for a fin-type HS by utilizing Al 2 O 3 /water nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Different manufacturing techniques also play an important role in the design of heat sinks; for example, pin-type geometry with addi-tive manufacturing was designed and its effects analyzed [10]. Thangavel and Sekar [11] designed a lotus-type heat sink, analyzed the temperature distributions in laminar and turbulent flow, and observed that they decreased up to 302 K. Nanofluids (NFs) are being used more and more to improve heat transfer in different HS setups because to their high thermal conductivity and density. The computational study conducted by Kavitha et al [12] demonstrated a significant 68% enhancement in heat transfer for a fin-type HS by utilizing Al 2 O 3 /water nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to use cooling agents. However, a significant specific gravity (8.6 g/cm 3 ) does not allow the use of such materials in products intended for flight [17].…”
Section: Introductionmentioning
confidence: 99%